Comparison of Nazief–Adriani and Porter Stemmer in Determining Javanese Root Words - Anggi Ayu Maharani; Fadhli Almu’iini Ahda (Journal of Information System Research (JOSH), 2026)
Stemming is an important step in text processing to convert inflected words into their root word. In Javanese, the stemming process is more challenging due to its complex morphological characteristics, including prefixes, infixes, suffixes, and combinations of affixes that are often accompanied by phonological changes. This study aims to compare the performance of the Nazief–Adriani and Porter Stemmer algorithms in Javanese stemming by including infix processing as part of the stemming stage. The dataset used consists of 603 Javanese affixed words covering various types of affixes. The evaluation was conducted using a confusion matrix with accuracy, precision, recall, and F1-score metrics, as well as an analysis of over-stemming and under-stemming errors. The results show that the Nazief–Adriani algorithm performs better with an accuracy of 90.05%, compared to the Porter Stemmer, which achieved 76.12%. This advantage is influenced by the validation of the dictionary at each stage of affix cutting, so that the stemming results are more controlled. The application of infix processing has also been proven to contribute to improving the accuracy of stemming results. This study is expected to be a reference in the development of natural language processing systems for Javanese and encourage further research related to the refinement of morphological rules.